Analisis Perubahan Tekanan Air Pori pada Tanah Lunak akibat Beban Trial Embankmentdengan menggunakan Plaxis Versi 7.2. - Patria, Adhe Noor; Suryolelono, Kabul Basah; Suhendro, Bambang (Jenderal Soedirman University, 2009)
Soft soil could be found easily in Indonesia. Constructions that built on this soil; such as embankment; face someÂ obstructions, for instance long period consolidation, difficult soil compaction, unstable slope of embankment and high settlement value for long period. Consolidation related to particle size of soil grains, soil permeability coefficient and pore size between soil particles. This research was carried out with numerical simulation and aimed to analyze the change in pore water pressures in soft soil due to embankment load.Numerical simulation was carried out by using Plaxis version 7.2. The time periods for construction and consolidation were the same with field measurement values. Total times for both stages were 102 days. Material model used were Mohr Coulomb Model and input materialÂ model that were used were the same with filed measurement values.The results showed that at the end of construction stage there always an increasement in pore water pressure (excess pore water pressureÂ existed) and the decreasement of pore water pressure occurred in consolidation period. Excess pore water pressures of soil below embankment were at area A, depth 0,5 was -22,8093 kPa, at area B (depth 9 m) was -21,5576 kPa and at area C (depth 13 m) was -14,159 kPa.